Kinematics differences between personal best and worst throws in actual javelin competition. (2nd January 2020) - Chen, Yo; Chou, Yi-Chen; Lo, Tang-Yun; Chang, Wen-Hsing; Chang, Jia-Hao
ABSTRACT: This study examined kinematics differences between personal best and worst throws to determine movement corrections for javelin throwers. Eight elite Asian male throwers were filmed as participants in Taipei Athletics Open 2015 (age: 22.1 ± 2.2 years, height: 177.3 ± 3.3 cm, and weight: 82.1 ± 3.5 kg). A high-speed camera with a 300-Hz sampling rate was used to collect motion images in the sagittal plane. Three-dimensional software was used to digitise and analyse the kinematics of throwing images. The Wilcoxon two-sample test was used to compare the throwing posture and javelin kinematics for the longest and shortest throws. The statistical significance was set at α = .05. Javelin travel distance was 70.9 ± 5.9 m and 67.2 ± 6.3 m in longest (best) and shortest (worst) throws. The wrist velocity at release was greater in longest throws (22.7 ± 0.8 m/s), with lower velocity in shortest throws (21.6 ± 0.5 m/s). A greater elbow joint angle was found in the longest throw group. The joint angle was 166.7 ± 10.6° and 158.4 ± 13.5° in longest and shortest throw groups, respectively. Throwers can improve distance by extending the elbow to accelerate the forearm when releasing.